A tough hydrogel prepared by DETA / NaOH synergistic initiation and a preparation method and application thereof
Patent Information
- Application Number
- CN202611406190.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于提供一种DETA/NaOH协同引发制备的强韧水凝胶及其制备方法和应用,以解决现有水凝胶制备中聚合速率与网络均匀性难以兼顾、力学性能不足的技术问题
(1)实现了低碱用量条件下的室温快速凝胶化。单独使用NaOH时,需较高的碱用量才能有效引发聚合,碱用量低于阈值时体系无法凝胶。本发明通过引入DETA与NaOH协同,在NaOH用量降至1.5mL~2.8mL(30wt%溶液)时,体系仍能在室温下数分钟到数十分钟内完成凝胶化,显著降低了碱用量阈值,拓宽了配方调控空间。
Smart Images

Figure CN122878485A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional polymer materials technology, and relates to a hydrogel material, specifically a strong and tough hydrogel prepared by DETA / NaOH synergistic initiation, its preparation method and application. Background Technology
[0002] Hydrogels are three-dimensional cross-linked soft materials composed of a hydrophilic polymer network and water. Due to their flexibility and tunable physicochemical properties, they have broad application prospects in wearable electronics and flexible sensing. Free radical polymerization is one of the most commonly used methods for preparing hydrogels, but hydrogels prepared by traditional free radical polymerization often suffer from intrinsic defects such as inhomogeneous network structure, making it difficult to achieve both material strength and toughness. In addition, traditional preparation processes often require external energy stimulation (such as ultraviolet irradiation or heating) or rely on toxic chemical additives, which is time-consuming and cumbersome.
[0003] To address these issues, researchers have developed various strategies. Controlled radical polymerization techniques (such as ATRP and RAFT) can improve network uniformity, but the reaction time is typically several hours to tens of hours, and there is a lack of effective energy dissipation mechanisms, resulting in materials with insufficient toughness. Toughening strategies such as introducing a second network or post-salting treatment are cumbersome and difficult to achieve integrated molding at room temperature. The exothermic neutralization reaction of inorganic bases (such as sodium hydroxide) with acidic monomers can be used to drive polymerization, but the amount of inorganic base needs to reach a certain threshold to effectively initiate gelation; below this threshold, the system cannot complete polymerization at room temperature, limiting the flexibility of formulation control. Polyamines are commonly used as crosslinking agents in polymer materials, forming charge-assisted hydrogen bonds with carboxyl groups on polyacrylic acid chains to enhance the network structure. Redox systems of persulfates and amines have also been used to accelerate polymerization, such as the combination of tetramethylethylenediamine and ammonium persulfate; however, in existing reports, amines are only used as redox promoters, and their function as dynamic crosslinking agents participating in network construction has not yet been systematically utilized.
[0004] Therefore, it remains of great significance to develop a method for preparing hydrogels that can achieve rapid gelation at room temperature with low alkali content, while possessing excellent mechanical properties and network uniformity. Summary of the Invention
[0005] The purpose of this invention is to provide a strong and tough hydrogel prepared by DETA / NaOH synergistic initiation, its preparation method and application, so as to solve the technical problems of insufficient mechanical properties and difficulty in achieving both polymerization rate and network uniformity in the preparation of existing hydrogels.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The first objective of this invention is to provide a method for preparing strong and tough hydrogels through DETA / NaOH synergistic initiation, specifically comprising the following steps: (1) Dissolve the acidic monomer, neutral monomer, N,N'-methylenebisacrylamide solution, initiator and a certain amount of DETA in deionized water in proportion and stir evenly to obtain the precursor solution; (2) Add NaOH solution to the precursor solution, shake quickly and let stand at room temperature. Gelification will be completed within a few minutes.
[0007] Furthermore, the acidic monomer is acrylic acid or 2-acrylamido-2-methylpropanesulfonic acid (AMPS), the neutral monomer is acrylamide, and the initiator is ammonium persulfate or potassium persulfate.
[0008] Furthermore, the mass ratio of the acidic monomer to the neutral monomer is (1-2):1.
[0009] Furthermore, the concentration of the N,N'-methylenebisacrylamide solution is 2 mg / mL, and the ratio of the amount of N,N'-methylenebisacrylamide solution added to the total mass of the monomer is 0.44 mL: (2-3) g.
[0010] Furthermore, the amount of DETA used is 21-63 μL.
[0011] Furthermore, the concentration of the NaOH solution is 30 wt%, and the amount used is 1.5-2.8 mL.
[0012] Furthermore, the gel formation time was 1.33-35.50 min.
[0013] A second objective of this invention is to provide a strong and tough hydrogel prepared by the method described above.
[0014] A third objective of this invention is to provide the application of the aforementioned strong hydrogel in multi-channel flexible sensing.
[0015] Compared with the prior art, the beneficial effects of this invention are: (1) Rapid gelation at room temperature under low alkali dosage conditions was achieved. When using NaOH alone, a relatively high alkali dosage is required to effectively initiate polymerization, and the system cannot gel when the alkali dosage is below the threshold. By introducing DETA in synergy with NaOH, the system can still complete gelation within a few minutes to tens of minutes at room temperature when the NaOH dosage is reduced to 1.5 mL to 2.8 mL (30 wt% solution), which significantly reduces the alkali dosage threshold and broadens the formulation control space.
[0016] (2) Dual-path synergistic polymerization with high polymerization efficiency. This invention utilizes the heat of neutralization reaction between NaOH and acrylic acid to drive the thermal decomposition of APS (thermal initiation path) and the redox reaction between DETA and APS to generate free radicals (chemical initiation path). The two paths work synergistically, and gelation can be completed within minutes at room temperature without external heating or ultraviolet irradiation.
[0017] (3) Multiple dynamic crosslinking endows the hydrogel with excellent mechanical properties. The polyamine groups of DETA form charge-assisted hydrogen bonds (-NH3) with carboxylate groups in situ. + ...-OOC - ), while NaOH introduces Na + It forms an electrostatic interaction with the carboxylate group (-COO). - ···Na + The synergistic effect of two dynamic crosslinking mechanisms endows the hydrogel with excellent mechanical properties.
[0018] (4) Uniform and dense network structure. In this invention, the polymerization rate and crosslinking formation are highly synchronized, and the resulting hydrogel has a dense and uniform micro-network structure, avoiding network defects caused by the mismatch between chain growth and crosslinking kinetics in traditional free radical polymerization.
[0019] (5) Simple operation, inexpensive raw materials, and environmentally friendly. The entire process of this invention is carried out at room temperature, without the need for external heating, ultraviolet irradiation, or toxic chemical additives, and gelation can be completed within minutes. All raw materials used are bulk chemical products, without the need for nanofillers or precious metal salts, resulting in low cost and suitability for large-scale production.
[0020] (6) High functional integration. The hydrogel prepared by this invention has excellent mechanical properties, electrical conductivity and adhesion properties, with an electrical conductivity of up to 4 S / m. It can be assembled into a flexible strain sensor for multi-channel gesture recognition. Attached Figure Description
[0021] Figure 1 The temperature evolution diagrams are for the reaction system during the preparation of hydrogels in Examples 1-3.
[0022] Figure 2 The temperature evolution diagrams are shown for the reaction systems during the preparation of hydrogels in Examples 2 and 4-7.
[0023] Figure 3 The images show the electron paramagnetic resonance (ESR) results at 30s and 120s during the preparation of the hydrogel in Example 3.
[0024] Figure 4 The image shows the ESR results at 120s during the hydrogel preparation process in Examples 1-3.
[0025] Figure 5Stress-strain diagrams of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-2.
[0026] Figure 6 SEM images of the hydrogels prepared in Example 2 and Comparative Example 2.
[0027] Figure 7 The hydrogel prepared in Example 2 is used as a flexible sensor in a multi-channel sensing image on multiple fingers. Detailed Implementation
[0028] Unless otherwise specified, all raw materials and reagents used in the specific embodiments of this invention are commercially available products.
[0029] Example 1
[0030] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 21μL of diethylenetriamine and dissolve them in 5.12g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.5 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0031] Example 2
[0032] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine and dissolve them in 5.12g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.5 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0033] Example 3
[0034] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 63μL of diethylenetriamine and dissolve them in 5.12g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.5 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0035] Example 4
[0036] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine and dissolve them in 6.12g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 1.5 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0037] Example 5
[0038] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine and dissolve them in 5.92g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 1.7 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0039] Example 6
[0040] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine and dissolve them in 5.62g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.0 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0041] Example 7
[0042] S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine and dissolve them in 4.82g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.8 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0043] Example 8
[0044] S1. Weigh out 4g AMPS, 2g acrylamide, 0.88mL N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g MBA), 0.1g ammonium persulfate and 42μL diethylenetriamine and dissolve them in 5.12g deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.5 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature to complete gelation.
[0045] In this embodiment, since the molecular weight of AMPS (approximately 207) is significantly greater than that of acrylic acid (72), in order to keep the number of moles of polymerizable functional groups (carbon-carbon double bonds and sulfonic acid groups) in the system basically equivalent to that of the acrylic acid system (2g AA), the amount of AMPS is adjusted to 4g.
[0046] Comparative Example 1 S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine, and dissolve them in 4.82g of deionized water to obtain a homogeneous mixed solution. Let it stand at room temperature and observe the gelation phenomenon.
[0047] Comparative Example 2 S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA), 0.1g of ammonium persulfate and 42μL of diethylenetriamine and dissolve them in 4.82g of deionized water to obtain a homogeneous mixed solution.
[0048] S2. Place the above solution in a 60℃ water bath and observe the gelation phenomenon.
[0049] Comparative Example 3 S1. Weigh out 2g of acrylic acid, 2g of acrylamide, 0.88mL of N,N'-methylenebisacrylamide solution (2mg / mL, containing 0.00176g of MBA) and 0.1g of ammonium persulfate, and dissolve them in 5.62g of deionized water to obtain a homogeneous mixed solution A. S2. Use a pipette to quickly add 2.5 mL of sodium hydroxide solution (30 wt%) to the above precursor solution, vortex mix for about 20 seconds, and let stand at room temperature.
[0050] Temperature changes during the preparation of hydrogels in the examples and comparative examples were monitored using a thermal infrared molding apparatus. The initial room temperature and the temperature change instantaneously after the addition of sodium hydroxide solution were recorded. The gelation time was determined using the inversion method. The results are shown in Table 1.
[0051] Table 1. Initial temperature data and gel formation time of Examples 1-8 and Comparative Examples 1-3
[0052] Initial temperature refers to the temperature reached by the system instantaneously after the sodium hydroxide solution is added.
[0053] As shown in Table 1, the gel formation time for Examples 1-8 ranged from 1.33 min to 35.50 min. The gel time decreased with increasing DETA or NaOH dosage. When the DETA dosage increased from 21 μL to 63 μL (Examples 1-3, NaOH dosage was 2.5 mL), the gel time decreased from 7.94 min to 3.00 min; when the NaOH dosage increased from 1.5 mL to 2.8 mL (Examples 2, 4-7, DETA dosage was 42 μL), the gel time decreased from 35.50 min to 1.33 min. In Example 8, AMPS was used instead of acrylic acid as the acidic monomer, with 4 g of AMPS and 2 g of acrylamide (not in equal mass ratio). The gel time was 6 min, comparable to Example 2 (acrylic acid system, gel time 5.22 min). This indicates that the DETA / NaOH synergistic initiation system of this invention is also applicable to AMPS-based acidic monomers.
[0054] Regarding the initial temperature, the initial temperature in Examples 1-7 increased with increasing NaOH dosage. When the NaOH dosage was 2.8 mL, the initial temperature reached 48.3 °C, while when the NaOH dosage was 1.5 mL, the initial temperature was only 38.5 °C. This indicates that the initial temperature rise mainly originated from the exothermic neutralization reaction between NaOH and acrylic acid. When the NaOH dosage was fixed (Examples 1-3), the initial temperatures remained essentially consistent (47.1-48.8 °C), further confirming that the initial temperature rise was independent of DETA and determined solely by the NaOH dosage.
[0055] Example 8 uses AMPS instead of acrylic acid, with an initial temperature of approximately 37.0°C, lower than the initial temperature of the acrylic acid system with the same amount of NaOH (Examples 1-3, 47.1-48.8°C). This is because AMPS has a larger molecular weight (approximately 207), and the number of sulfonic acid groups in 4g of AMPS (approximately 0.0193 mol) is lower than the number of carboxyl groups in 2g of acrylic acid (approximately 0.0278 mol), resulting in a corresponding reduction in the exothermic reaction of neutralization. Nevertheless, the system can still complete gelation within 6 minutes, indicating that the DETA / NaOH synergistic initiation strategy of this invention can still effectively drive polymerization under lower neutralization heat conditions, further demonstrating the good adaptability of this method to different types of acidic monomers and changes in neutralization heat.
[0056] In Comparative Example 1, without the addition of NaOH, there was no initial temperature rise, and gelation did not occur within 5 hours at room temperature, but began to slowly gel after 5 hours. In Comparative Example 2, the system of Comparative Example 1 was placed in a 60°C water bath, and gelation was completed within 6 minutes. In Comparative Example 3, no DETA was added, only 2.5 mL of sodium hydroxide was added, and the initial temperature was 47.5°C (comparable to Examples 1-3), but gelation still failed after more than 8 hours. The above results indicate that the heat of neutralization alone is insufficient to achieve gelation, and external heat can replace the role of the heat of neutralization, but both require the presence of DETA to complete gelation at room temperature.
[0057] Combined with Table 1 Figure 1-2 It can be seen that when the amount of NaOH is fixed, the initial temperature is basically the same, but the increase of DETA dosage leads to a shorter gelation time (Examples 1-3), indicating that DETA provides additional free radicals through the redox pathway, forming a synergy with the thermal decomposition pathway generated by the heat of neutralization. When the amount of NaOH is increased, the initial temperature rises and the gelation time shortens (Examples 2, 4-7), indicating that the intensity of the heat of neutralization directly affects the initiation efficiency. Although the initial temperature of Comparative Example 3 is comparable to that of Examples 1-3, the system cannot gel due to the lack of the redox pathway provided by DETA, further confirming the necessity of the synergy between DETA and NaOH.
[0058] Figure 3 Free radical detection results showed that in Example 3, free radical signals could be detected 30 seconds after the addition of NaOH during the polymerization reaction, and the signal significantly increased at 2 minutes, confirming that the initial neutralization heat could trigger the decomposition of ammonium persulfate to generate free radicals, and the subsequent exothermic polymerization further accelerated the initiation process. The free radical signal intensity at 120 seconds was compared with that in Examples 1-3. Figure 4 The higher the DETA dosage, the stronger the signal, confirming that the redox reaction between DETA and ammonium persulfate contributes additional free radicals. These results collectively indicate that the synergistic effect of thermal initiation and redox initiation pathways in the system of this invention is the main reason for achieving rapid gelation under low alkali conditions.
[0059] The hydrogels prepared in the examples and comparative examples were subjected to uniaxial tensile property tests. The sample size was 30 mm × 10 mm × 6 mm, the tensile speed was 100 mm / min, and the tests were conducted using an electronic universal testing machine (Shanghai Hengyi Precision Instrument Co., Ltd.). The results are shown in Table 2.
[0060] Table 2. Mechanical properties of the hydrogels in Examples 1-8 and Comparative Examples 1-3
[0061] Note: Comparative Example 3 was not tested for mechanical properties because it could not form a stable gel.
[0062] From Table 2 and Figure 5 It can be seen that the tensile strength of Examples 1-7 ranges from 81.40 kPa to 206.53 kPa, and the toughness is 1535.50 kJ / m. 3 Up to 3484.94 kJ / m 3 Both were significantly better than Comparative Example 1 (60.77 kPa, 305.99 kJ / m²). 3 ) and Comparative Example 2 (47.86 kPa, 225.21 kJ / m 3 ).
[0063] Taking Examples 1-3 as examples, their tensile strengths are 206.53 kPa, 180.10 kPa, and 105.64 kPa, respectively, and their toughnesses are 2617.62 kJ / m, respectively. 3 3484.94 kJ / m 3 and 1535.50 kJ / m 3 Compared with Comparative Example 1, the tensile strength increased by approximately 3.4 times and the toughness increased by approximately 8.5-11.4 times; compared with Comparative Example 2, the tensile strength increased by approximately 2.2-4.3 times and the toughness increased by approximately 6.8-15.5 times.
[0064] Example 8 uses AMPS instead of acrylic acid (4g, mass ratio of AMPS to acrylamide 2:1), and its tensile strength is 92.8kPa and its toughness is 934.96kJ / m. 3 Although this value is slightly lower than that of Examples 1-7, it is still significantly better than that of Comparative Example 1 (60.77 kPa, 305.99 kJ / m). 3 ) and Comparative Example 2 (47.86 kPa, 225.21 kJ / m 3 The tensile strength increased by approximately 52.7% and 93.9%, respectively, and the toughness increased by approximately 2.1 times and 3.2 times, respectively. These results demonstrate that AMPS, as an acidic monomer, can also achieve effective polymerization and crosslinking under the DETA / NaOH synergistic initiation system of this invention. Although its mechanical properties are slightly lower than those of the acrylic acid system due to differences in monomer structure (AMPS has a larger molecular weight and different coordination abilities between sulfonic acid and carboxylic acid groups), they are significantly superior to traditional single thermal initiation or single redox initiation methods, fully verifying the applicability and effectiveness of the method of this invention for AMPS-type acidic monomers.
[0065] The cross-sectional morphology of the hydrogels of Example 2 and Comparative Example 2 was observed using scanning electron microscopy (SEM), and the results are as follows: Figure 6 As shown. By Figure 6As can be seen, the hydrogel of Example 2 exhibits a dense and uniform three-dimensional porous network structure with pore sizes of approximately several hundred nanometers, and no obvious macroporous defects or polymer agglomeration were observed. This uniform network structure facilitates the uniform transmission of stress within the material, avoiding localized stress concentration, thereby endowing the hydrogel with excellent mechanical properties. In contrast, the hydrogel network structure of Comparative Example 2 is significantly loose, with pore sizes exceeding twenty micrometers and varying in size. This non-uniform network structure easily becomes a weak point for crack initiation and propagation under external forces, resulting in significantly lower mechanical properties compared to Example 2. The above microstructure comparison confirms that the highly synchronized matching of polymerization rate and crosslinking formation under the DETA / NaOH synergistic initiation system of this invention is the key structural basis for forming a uniform and dense network structure, thereby achieving a significant improvement in mechanical properties.
[0066] A comparison of the mechanical properties of Examples 1-8 and Comparative Examples 1-2 shows that the synergistic effect of DETA and NaOH significantly improves the mechanical properties of the hydrogel. This can be attributed to the following three aspects: First, the network structure is enhanced by multiple dynamic cross-links. DETA has a tridentate amine structure, and its amine groups can form charge-assisted hydrogen bonds (-NH3) with carboxylate groups on the polymer chain. + ...-OOC - ), forming strong cross-linking points; at the same time, NaOH introduces Na + An electrostatic interaction (-COO) is formed with the carboxylate group. - ···Na + These crosslinking elements also participate in network construction as crosslinking points. The synergistic effect of these two crosslinking processes effectively increases the crosslinking density, thereby significantly enhancing the toughness and fracture strength of the hydrogel.
[0067] Second, the synergistic initiation of the two pathways enhances the efficiency of free radical generation. The exothermic neutralization reaction between NaOH and acrylic acid drives the thermal decomposition of ammonium persulfate, while a redox reaction occurs between DETA and ammonium persulfate to generate free radicals. The synergistic effect of these two initiation pathways improves the efficiency of free radical generation in the system. More free radicals participating in the polymerization reaction are beneficial for forming a more uniform and dense network structure.
[0068] Third, the multiple dynamic non-covalent bonds endow the material with excellent energy dissipation capabilities. The dynamic crosslinking between DETA and sodium ions and carboxylate groups, as well as the hydrogen bonding interactions between amide, carboxylate, and amine groups, collectively endow the hydrogel with multiple dynamic non-covalent bonds. Under external forces, these dynamic bonds can dissipate energy through reversible breakage and recombination, thereby effectively improving the toughness of the hydrogel.
[0069] The conductivity of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-2 was tested using the AC impedance method. The hydrogel samples were cut into 30mm × 30mm × 6mm pieces and placed between two copper electrodes. The test was conducted within the frequency range of 0.1Hz to 1MHz, and the conductivity was calculated using the following formula: σ = L / (R×S) Where σ is the conductivity (S / m), L is the sample thickness (m), R is the resistance (Ω), and S is the electrode area (m²). 2 The results are shown in Table 3.
[0070] Table 3 shows the conductivity test results of Examples 1-3 and Comparative Examples 1-2.
[0071] As shown in Table 3, the conductivity of Examples 1-3 is significantly higher than that of Comparative Examples 1-2, indicating that the hydrogel prepared by the present invention has good ionic conductivity and can effectively transmit electrical signals when assembled into a flexible strain sensor.
[0072] To clarify the synergistic effective range of DETA and NaOH in this invention, the formulation boundaries were investigated. If the DETA dosage exceeds 63 μL (e.g., 84 μL), the polymerization reaction is too vigorous when the NaOH dosage is 2.5 mL, releasing a large amount of heat in a short time, leading to explosive polymerization. The resulting product is brittle, hard, and heterogeneous, unsuitable for use as a flexible sensing material. If the DETA dosage is less than 21 μL (e.g., 10 μL), the redox initiation pathway contributes insufficiently, significantly prolonging the gelation time. Similarly, when the NaOH dosage exceeds 2.8 mL (e.g., 3.5 mL), the neutralization reaction is excessively exothermic, causing explosive polymerization. When the NaOH dosage is less than 1.5 mL (e.g., 1.0 mL), the initial neutralization heat is insufficient to effectively trigger the decomposition of ammonium persulfate, and the system cannot complete gelation at room temperature for an extended period. These boundary results indicate that only within the formulation range defined in this invention can the synergistic matching of thermal initiation and redox initiation be achieved, resulting in a hydrogel with both rapid molding and excellent mechanical properties.
[0073] The hydrogel obtained in Example 2 was cut into sensing units of appropriate size and attached to the knuckles of the operator's five fingers. Each sensing unit was connected to a multi-channel data acquisition module via wires, and the resistance signal was transmitted to the terminal device in real time via a wireless communication module. When the operator performs different gestures (such as clenching a fist, extending, bending a single finger, or multiple finger combinations), the degree of bending of each finger is different, causing tensile strain in the corresponding hydrogel sensor, and its resistance value changes accordingly. The system synchronously records the relative resistance change curve (ΔR / R0) of each channel, and the results are as follows. Figure 7As shown in the figure, different channels corresponding to different gestures all generate distinguishable and stable resistance signals, and the signal peak value remains stable during the cyclic test, indicating that the hydrogel of the present invention has high stability and repeatability as a flexible sensor.
Claims
1. A method for preparing strong and tough hydrogels through DETA / NaOH synergistic initiation, characterized in that: Specifically, the following steps are included: (1) Dissolve the acidic monomer, neutral monomer, N,N'-methylenebisacrylamide solution, initiator and DETA in deionized water and stir until homogeneous to obtain the precursor solution; (2) Add NaOH solution to the precursor solution, shake quickly and let stand at room temperature. Gelification will be completed within a few minutes.
2. The method for preparing strong and tough hydrogels by DETA / NaOH synergistic initiation according to claim 1, characterized in that: The acidic monomer is acrylic acid or 2-acrylamido-2-methylpropanesulfonic acid, the neutral monomer is acrylamide, and the initiator is ammonium persulfate or potassium persulfate.
3. The method for preparing strong and tough hydrogels by DETA / NaOH synergistic initiation according to claim 1, characterized in that: The mass ratio of the acidic monomer to the neutral monomer is (1-2):
1.
4. The method for preparing strong and tough hydrogels by DETA / NaOH synergistic initiation according to claim 1, characterized in that: The concentration of the N,N'-methylenebisacrylamide solution is 2 mg / mL, and the ratio of the amount of N,N'-methylenebisacrylamide solution added to the total mass of the monomer is 0.44 mL: (2-3) g.
5. The method for preparing strong and tough hydrogels by DETA / NaOH synergistic initiation according to claim 1, characterized in that: The amount of DETA used is 21-63 μL.
6. The method for preparing strong and tough hydrogels by DETA / NaOH synergistic initiation according to claim 1, characterized in that: The concentration of the NaOH solution is 30 wt%, and the amount used is 1.5-2.8 mL.
7. The method for preparing strong and tough hydrogels by DETA / NaOH synergistic initiation according to claim 1, characterized in that: The gel formation time was 1.33-35.50 min.
8. A strong and tough hydrogel prepared by the preparation method according to any one of claims 1-7.
9. The application of a strong and tough hydrogel prepared by the preparation method according to any one of claims 1-7 in multi-channel flexible sensing.